THE STARTING TUG IS THE MOST IMPORTANT ELEMENT OF THE STARTING TECHNIQUE IN MAS-WRESTLING - Loginov V.N.; Vorobyev S.A.; Konstantinov N.E.; Agapov A.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the power of the start and the starting tug of mas-wrestlers, taking into account the structure and content of the starting actions. Methods and structure of the study. A video-computer analysis and tensoanalysis of the execution of the phase and structure of the technical element of the start in mas-wrestling by highly qualified athletes were carried out, the selection of the most effective elements of the start technique based on the data obtained was carried out. The starting position and thrust of the mas-wrestler, starting fixation (pressure) and starting tug when performing a power start were considered. Results and conclusions. Highly qualified athletes in mas-wrestling surpass qualified mas-wrestlers in terms of space-time and speed-strength parameters studied in the work. The revealed parameters of the features of the phase structure of the starting thrust can be recommended as a guideline and used as one of the criteria for assessing physical fitness for the requirements of this sport.